Aflatoxin B1-contaminated diet disrupts the blood–brain barrier and affects fish behavior: Involvement of neurotransmitters in brain synaptosomes - Baldissera M.D. (2018)
© 2018 Elsevier B.V.It is known that the cytotoxic effects of aflatoxin B1 (AFB1) in endothelial cells of the blood–brain barrier (BBB) are associated with behavioral dysfunction. However, the effects of a diet contaminated with AFB1 on the behavior of silver catfish remain unknown. Thus, the aim of this study was to evaluate whether an AFB1-contaminated diet (1177 ppb kg feed−1) impaired silver catfish behavior, as well as whether disruption of the BBB and alteration of neurotransmitters in brain synaptosomes are involved. Fish fed a diet contaminated with AFB1 presented a behavioral impairment linked with hyperlocomotion on days 14 and 21 compared with the control group (basal diet). Neurotransmitter levels were also affected on days 14 and 21. The permeability of the BBB to Evans blue dye increased in the intoxicated animals compared with the control group, which suggests that the BBB was disrupted. Moreover, acetylcholinesterase (AChE) activity in brain synaptosomes was increased in fish fed a diet contaminated with AFB1, while activity of the sodium-potassium pump (Na+, K+-ATPase) was decreased. Based on this evidence, the present study shows that silver catfish fed a diet containing AFB1 exhibit behavioral impairments related to hyperlocomotion. This diet caused a disruption of the BBB and brain lesions, which may contribute to the behavioral changes. Also, the alterations in the activities of AChE and Na+, K+-ATPase in brain synaptosomes may directly contribute to this behavior, since they may promote synapse dysfunction. In addition, the hyperlocomotion may be considered an important macroscopic marker indicating possible AFB1 intoxication.